Development of 3D skin equivalents for application in photodynamic biostimulation therapy assays using curcumin nanocapsules - Amantino, Camila F. [UNESP]; do Amaral, Stéphanie R. [UNESP]; Aires-Fernandes, Mariza [UNESP]; Oliani, Sonia M. [UNESP]; Tedesco, Antonio C.; Primo, Fernando L. [UNESP] (Elsevier, 2024)
For decades, animal models have been the standard approach in drug research and development, as they are required by regulations in the transition from preclinical to clinical trials. However, there is growing ethical and scientific concern regarding these trials, as 80 % of the therapeutic potential observed in pre-clinical studies are often unable to be replicated, despite demonstrating efficacy and safety. In response to this, Tissue Engineering has emerged as a promising alternative that enables the treatment of various diseases through the production of biological models for advanced biological assays or through the direct development of tissue repairs or replacements. One of the promising applications of Tissue Engineering is the development of three-dimensional (3D) models for in vitro tests, replacing the need for in vivo animal models. In this study, 3D skin equivalents (TSE) were produced and used as an in vitro model to test photobiostimulation using curcumin-loaded nanocapsules. Photodynamic biostimulation therapy uses photodynamic processes to generate small amounts of reactive oxygen species (ROS), which can activate important biological effects such as cell differentiation, modulation of inflammatory processes and contribution to cell regeneration. The PLGA nanocapsules (NC) used in the study were synthesized through a preformed polymer deposition method, exhibiting particle size <200 nm, Zeta potential >|30| and polydispersity index between 0.5 and 0.3. Atomic force microscopy analyzes confirmed that the particle size was <200 nm, with a spherical morphology and a predominantly smooth and uniform surface. The NC biocompatibility assay did not demonstrate cytotoxicity for the concentrations tested (2.5–25 μg mL−1).The in vitro release assay showed a slow and sustained release characteristic of the nanocapsules, and cellular uptake assays indicated a significant increase in cellular internalization of the curcumin-loaded nanostructure. Monolayer photobiostimulation studies revealed an increase in cell viability of the HDFn cell line (viability 134 %–228 %) for all LED fluences employed at λ = 450 nm (150, 300, and 450 mJ cm−2). Additionally, the scratch assays, monitoring in vitro scar injury, demonstrated more effective effects on cell proliferation with the fluence of 300 mJ cm−2. Staining of TSE with hematoxylin and eosin showed the presence of cells with different morphologies, confirming the presence of fibroblasts and keratinocytes. Immunohistochemistry using KI-67 revealed the presence of proliferating cells in TSE after irradiation with LED λ = 450 nm (150, 300, and 450 mJ cm−2).
Keywords: Curcumin; Nanocapsules; Photodynamic biostimulation therapy; Three-dimensional skin equivalents; Tissue engineering